(3aj GdJGQjN GdGbJUGOj (B/s - (3GdOShbj, YGUe, s ([(3Ohf ecGf(B]: s (3eDSSI GHf NdOhf(B, s, 1999)
(3jJfGhd GdcJGH eQMdI GdYUhQ GdbOjeI ,eQMdI GdYUhQ GdhSWi, GdYUQ GdMOjK , GdJbOe GdUfGYj h GdRQGYj , Jbhje GdQGSeGdjI , GdfXGe GdGTJQGcj(B.s
(3HHdjhZQGajG U(B.206s
Keywords: (3GdJGQjN GdGbJUGOjs; (3GdQCSeGdjIs